Control interno basado en la gestión de riesgos y su incidencia en el cumplimiento de planes y programas del área de gestión de talento humano del Gobierno Autónomo Descentralizado Municipal del cantón Ventanas año 2017 - Ortíz Mosquera, César Geovanny (2018)
Enterprise Risk Management has been gaining importance within public institutions, which operate in an increasingly demanding environment. Since it provides tools, which allow anticipating the negative events that occur in the processes of each functional area. The objective of this study was to evaluate the internal control based on risk management, and its impact on compliance with the plans and programs of the human talent area of the Autonomous Decentralized Government of the Ventanas canton. The methodology used was based on a survey of 165 public officials, a questionnaire with the eight components of COSO ERM related to the activities of the object of study. A structured interview with the Director of Human Talent Management, within a non - experimental diagnostic - evaluative analysis of a descriptive type, and an exploratory study. The results of this research show that a high percentage of public officials have weaknesses in the knowledge of strategies, mission and training through training. This fact is evident, with the absence of a formal business risk management system, which allows identifying and mitigating present and future risks. In conclusion, the evaluation of internal control, with the COSO ERM methodology to the area of human talent, determined a moderate level of confidence, which is why it is necessary to strengthen the components related to Risk Management and take corrective actions that contribute to the compliance with the proposed plans and programs. Key Words: Enterprise Risk Management, COSO ERM, Public Institutions, Plans and Programs, Human Talent, Public Officials